PENGENALAN BUDIDAYA IKAN DENGAN WADAH KARAMBA JARING APUNG BAGI SISWA KELAS IX SMP KRISTEN REHOBOTH AMBON - Fendjalang, Sophia N. M.; Rijoly, Stefanno M. A; Pattinasarany, Agapery Y; Pattipeilohy, Christian E. (Universitas Mataram, 2024)
The cultivation of fish has a charm that attracts the attention of students in class IX of SMP Kristen Rehoboth. This is evident in the students' enthusiasm to learn about fish cultivation using KJA containers, as well as practical ways to raise fish. Therefore, one of the holistic educations currently being developed at SMP Kristen Rehoboth is practical education about fish cultivation. Introducing freshwater cultivation to the students of SMP Kristen Rehoboth plays an important role in environmental education and practical learning. It allows students to understand directly the sustainability of aquatic biota, the importance of maintaining the balance of aquatic ecosystems, the role of fish in ecosystems, and the impact of human activities on aquatic environments. This activity is expected to have a positive impact on the understanding of SMP Kristen Rehoboth students regarding aquatic environments, and fish cultivation activities using floating net cages as fish farming containers. The activity consists of several stages, including preparation, implementation, and evaluation. In the implementation, the material presented includes: Understanding KJA and its differences from other fish cultivation containers; identifying the parts and functions of the KJA equipment components; and evaluating fish cultivation practices in KJA containers based on the results of practice. The post-test results show that 76.92% of students understand the material explained about KJA, and 70.77% of students have a good understanding of the material presented. These results indicate that students can understand the material given even though the delivery of the material is done simply. The enthusiasm of the students in class IX of SMP Kristen Rehoboth Ambon in participating in the introduction of fish cultivation using KJA shows that students are interested in learning about fish cultivation using floating net cages.